A conflict in Peru over trans-Pacific expansion: Álvaro de Mendaña's 1567 journey - Chalán Tejada, Diego A. (2010)
In Peru in the 1560s, a political conflict took place around the company of exploration and conquest of the South Pacific. In those years, a powerful group of encomenderos, far from resigning themselves to losing their repartimientos, sought to take possession of new lands and wealth on the other side of the ocean. In the opposite arena, the personal ambitions of the official in charge of consolidating the power of the Crown in Peru confronted him. That struggle was a manifestation of the colonial conflict of the time. In this case, the powerful encomendera family of the Maldonados and the governor of Peru, Lope García de Castro, would lead the struggle in 1567. The latter, using his political position, won thanks to the fact that he managed to ensure that his personal interests and those of the Crown coincided, in addition to the fact that, agilely, he managed to neutralize many of the political pretensions of a conflictive sector of the local encomendero elite.